Multiple origins of resistance-conferring mutations in Plasmodium vivax dihydrofolate reductase (2008)
ABSTRACT: Background: In order to maximize the useful therapeutic life of antimalarial drugs, it is crucial to understand the mechanisms by which parasites resistant to antimalarial drugs are selected and spread in natural populations. Recent work has demonstrated that pyrimethamine-resistance conferring mutations in Plasmodium falciparum dihydrofolate reductase (dhfr) have arisen rarely de novo, but spread widely in Asia and Africa. The origin and spread of mutations in Plasmodium vivax dhfr were assessed by constructing haplotypes based on sequencing dhfr and its flanking regions. Methods: The P. vivax dhfr coding region, 792 bp upstream and 683 bp downstream were amplified and sequenced from 137 contemporary patient isolates from Colombia, India, Indonesia, Papua New Guinea, Sri Lanka, Thailand, and Vanuatu. A repeat motif located 2.6 kb upstream of dhfr was also sequenced from 75 of 137 patient isolates, and mutational relationships among the haplotypes were visualized using the programme Network. Results: Synonymous and non-synonymous single nucleotide polymorphisms (SNPs) within the dhfr coding region were identified, as was the well-documented in-frame insertion/deletion (indel). SNPs were also identified upstream and downstream of dhfr, with an indel and a highly polymorphic repeat region identified upstream of dhfr. The regions flanking dhfr were highly variable. The double mutant (58R/117N) dhfr allele has evolved from several origins, because the 58R is encoded by at least 3 different codons. The triple (58R/61M/117T) and quadruple (57L/61M/117T/173F, 57I/58R/61M/117T and 57L/58R/61M/117T) mutant alleles had at least three independent origins in Thailand, Indonesia, and Papua New Guinea/Vanuatu. Conclusion: It was found that the P. vivax dhfr coding region and its flanking intergenic regions are highly polymorphic and that mutations in P. vivax dhfr that confer antifolate resistance have arisen several times in the Asian region. This contrasts sharply with the selective sweep of rare antifolate resistant alleles observed in the P. falciparum populations in Asia and Africa. The finding of multiple origins of resistance-conferring mutations has important implications for drug policy.